Analysing the Effect of Unequal Gap Spacing for Flow Past Over Three Rectangular Rods a Fixed Re (Reynolds Number) and Aspect Ratio (AR) - Islam, Shams-Ul; Manzoor, R.; Zahid, M.; Kulsoom, S.; Kausar, U. (Mathematics and Computer Science: Contemporary Developments Vol. 2, 2024)
Objectives: The present study examines the effect of unequal gap spacing for flow past over three rectangular rods a fixed Re (Reynolds number) and an Aspect Ratio (AR). Background: In computational fluid dynamics, the numerical study of flow past over a single or more than one object has a great impact on the scientific community for suitable selection of parameters such as Reynolds number, gap spacing, and Aspect ratio. Their suitable choice is used to control flow for the purpose of saving energy in order to avoid damaging of structure by reducing the fluid forces and to suppress the vortex shedding. Methodology: A two-dimensional (2-D) numerical study of flow over three rectangular Rods is conducted by using the Single Relaxation Time Lattice Boltzmann Method (SRTLBM). The gap spacing ( g ) between the rods is varied from 0.5 to 7 with a fixed Reynolds number i.e., Re = 150(Re = U \(∞\) d/v), (where U\(∞\) is uniform velocity, d is the size of an object and v is the kinematic viscosity) and aspect ratio AR = 0.25 (where, AR = 1/w,1 is the length and w is the width of the rods). Different flow structures, power spectra analysis of lift coefficients and force statistics are studied for this analysis at small, moderate and large gap spacing. Results: The present study revealed that the gap spacing between the rods has a great impact on the flow behavior. Therefore, different flow patterns are observed and some of them are outlined as, i). Shear layer reattachment (SLR), ii). Semi developed single bluff body (SDSBB), iii). Fully developed vortex shedding (FDVS), iv). Semi developed irregular vortex shedding, v) Fully generated two-row single bluff body, vi). Semi developed irregular single bluff body (SDISBB) and vii). Critical flow (CF) patterns. The critical flow behavior is observed at the gap spacing (g1,g2) = (5,2.5) , (here, g1 is the gap between upstream rods to middle one and g2 is the gap between middle rods to downstream rectangular rod). The power spectrum analysis of large wake regimes of different flow patterns showed distortion. Irregularities, multiple peaks and in some cases secondary peaks are also observed. Multi-peaks represent irregular behavior. While secondary peaks and distortion enable us to conclude that a critical flow pattern has been observed at certain points. In force statistics analysis, the values of Cdmean and Strouhal number are computed at different spacing ratios. The value of mean drag coefficients for all three rods at g1=3 is approximately the same, but at g1=1 and 5, the maximum value of Cdmean is observed for C2 as compared to C1 and C3, which is 6.91. Furthermore, Strouhal number values are much less than the single rod (SR) value for all three chosen small, moderate and large gap spacing values. The maximum value of St is examined at (g1,g2) = (1,1) i.e. 0.19. The amplitude of the values of the Strouhal number varied with the increase in the gap spacing. At critical flow, the Strouhal number has primary and secondary peaks, which depict the unsteadiness in the flow.